TEACHING THE STORY OF PROPHET NOAH WITH A LIVE STORY BOX APE FOR EARLY CHILDHOOD - Sari, Eky Adelia; Istiyani, Dwi (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to explore the potential of educational game tools (APE) live story box as an innovative learning media in conveying the story of the Prophet Noah to early childhood. The developed live story box combines elements of story, game, and technology, creating an immersive and interactive learning experience. Using a qualitative approach, through participatory observation, documentation, and in-depth interviews, this study analyzes children's responses to the live story box and identifies its benefits in increasing reading interest, developing imagination, and enriching their understanding of religious values. Data analysis techniques through narrative techniques. The results of the study indicate that the live story box has great potential as an effective Islamic religious learning tool, especially in instilling the values ​​of faith and submission to God. In addition, this study also emphasizes the importance of using media that is contextual and relevant to children's lives in the process of religious learning. These findings can be the basis for developing more interesting and effective religious learning strategies for children.